18-pulse Cascaded-Multilevel-Converter - Mehlmann, Gert; Svensson, Frederik; Herold, Gerhard (11th International Conference on Electrical Power Quality and Utilisation, 2011)
This paper presents an 18-pulse cascaded-multilevel-converter. With this inverter it is possible to generate AC voltages with low distortions in fundamental frequency modulation. Therefore differing voltage levels of multiple DC sources are added. Because of the topology of the inverter, all sources are balanced. © 2011 IEE
Keywords: harmonics; Multilevel-inverter; space phasor